Analisis Efisiensi Box Fermentasi Oncom Tahu dengan Sistem Arduino - Meri Rahmi; Agus Sifa; Rachmatullah - (Department of Mechanical Engineering, Universitas Andalas, 2022)
Tofu dregs are a by-product in the process of making tofu in solid form and are obtained from squeezed soybean pulp. Tofu pulp still has a relatively high protein content because in the process of making tofu not all protein content is extracted, especially when using a simple and traditional milling process. One of the products from tofu dregs is tofu oncom. Oncom is a fermented food product typical of West Java. Oncom is a processed food derived from soybeans, its nutritional value is almost the same as tofu and tempe. It contains protein and fat that are good for the body. The process of making tofu oncom is almost the same as making tempe oncom, However, its utilization is still small in the industry compared to its abundant production. So, a lot of it is still wasted. In addition, the process of making tofu oncom is still very simple and uses traditional methods by relying on natural conditions and this takes longer. For this reason, with better methods and technology, a fermentation box is made for the manufacture of tofu oncom. The method used is a heater and temperature and humidity sensors to speed up the fermentation process. In addition, the use of aluminum material, in order to ensure that oncom tofu is more hygienic so that it can become one of the traditional products that can compete in a better market. The results of this fermentation box indicate that the processing time for making tofu oncom is faster from 2 days (± 24 hours) to 1 day (± 14 hours). Reduction of processing time by about 58% so that productivity also increases to above 50% with a box capacity of up to 50 kg of tofu dregs.